Pengaruh Kepuasan kerja dan Komitmen Organisasional terhadap Keinginan Berpindah (Studi Empiris pada Profesional Sistem Informasi) - Rima Anggraini (JURNAL AKUNTANSI DAN KEUANGAN, 2012)
This study aimed to empirically investigates impact of job satisfaction and organizational commitment to turnover intent. The samples of this research are information system professional in Yogyakarta, Solo and Balikpapan. Data Collected use questioner. Regression is using to testing hypothesis. This research find a significantly impact of job satisfaction to turnover intent. But turnover intent is not influenced by organizational commitment.